FAKTOR-FAKTOR YANG MENENTUKAN LOYALITAS KARYAWAN DI HOTEL ADHIJAYA SUNSET - IWK.Teja Sukmana (Jurnal Ilmiah Hospitality Management, 2016)
This research aims to determine the factors that give variation to the employee loyalty at Adhijaya Sunset Hotel. The method used in collecting sample is census. The sample used on this research is 73 peoples as respondents. The result from questionnaire were tabulated and analyzed using SPSS software version 20.0 for windows.The result was obtained after doing the principal component analysis of 17 variables that affect the loyalty employee can be reduced to 5 factors. Each factor was named resposibility and apreciation with eigenvalue of 5.444; power and allowance with eigenvalue of 1607,flexible rule and recognition with eigenvalue of 1.403,management and oppoturnity to grow with eigenvalue of 1.393; Desire to satisfy the need by working hard with eigenvalue of 1.053. The most dominant factor is resposibility and apreciation with eigenvalue of 5.444, with 32.002 % of variance which was made up by the variables of desire to have recognition, status and resposibility, work environment condition, communication.Â